Exploring the Potential Use of Telehealth Technology to Improve the Diagnostic Process of Autism Spectrum Disorder (ASD) in Wales, United Kingdom - MANAHIL ALFURAYDAN (2021)
There is a significant delay between parents initially seeking help and receiving a diagnosis of Autism Spectrum Disorder (ASD). Telehealth has the potential to accelerate the ASD diagnostic pathway. However, user acceptance is essential for the successful implementation of telehealth technology. This thesis therefore aims to examine whether telehealth can be used to increase access to ASD diagnostic services in Wales and reduce the time taken to receive a diagnosis. To achieve this, a multimethod approach was adopted, comprising of three studies. Initially, a scoping review (Study1) was conducted examining the use of telehealth in ASD diagnostic assessment. This identified two methods: (a) Real-Time (b) Store-and-Forward, particularly the Naturalistic Observation Diagnostic Assessment (NODA) system. Results also suggest that telehealth is feasible and acceptable to the families. However, findings indicate that no study had thus far examined the factors of telehealth acceptance, based on theoretical foundation. Therefore, Studies two and three were conducted, to explore the parental experience of the diagnostic process, and investigate the predictors of their acceptance to use NODA for ASD diagnostic assessment, using the Unified Theory of Acceptance and Use of Technology model. Data for both studies was collected via an online questionnaire, targeting parents of children with ASD in Wales. Descriptive and inferential statistics were applied to the closed-ended questions, and thematic analysis was used for open-ended questions. Study 2 findings revealed that the majority of parents were dissatisfied with the diagnostic process, with the time taken to obtain a diagnosis being a predictor of their satisfaction. Study 3 found that the majority of parents felt positively towards the NODA, with their willingness to use the system being predicted by their age, performance expectancy, social influence and comfort with using laptop and smartphone devices. Implications and recommendations are further discussed at the end of the thesis.